Capitalism and Freedom: The Core of a Contradiction - An Essay on Cornelius Castoriadis and John McMurtry - Baruchello, Giorgio (Nordicum-Mediterraneum, 2008)
Capitalism and freedom is not only the title of a 1962 book by Milton Friedman playing a pivotal role in asserting worldwide the neoliberal paradigm, but also the slogan that leading statesmen, politicians and opinion-makers have been heralding in recent years, in order to justify, amongst other things, the slashing of welfare states and the invasion of foreign countries. Often, "capitalism" has been rephrased as "free trade" or "free market",[2] and coupled regularly with "democracy", this term denoting the political system that is believed to better entrench and promote "freedom" or "autonomy".[3] Thus, capitalism and democracy have been described as the two sides of one and the same project for human emancipation,[4] colouring the ideology and the political agenda of governments left and right, and showing how deeply neoliberal beliefs have become part of the dominant public mindset.